Księgowość gospodarstw rodzinnych i jej przydatność w podejmowaniu decyzji produkcyjnych - Bernacki, Andrzej; Wasilewski, Mirosław (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1999)
In this paper the author evaluated the suitability of accounting books keeping at family farms level considering an analysis of production and economic effects as well as decision-making process. This is the case of an accountancy scenario "Rolin". Author states that there is merited need for book keeping in private farms, mainly in commercial farms i.e. farms which market the bulk of their production and which note large production scale and high le vel of production intensity. On the basis of proposed method of on-farm analysis, it was found out that the holding obtained the highest level of farm income had maximal level of variable resources input. Additionally, both the farm income rate and the degree of covering of productive real fixed assets by flow of used variable means were the highest in the holding under consideration. Furthermore, indirect costs per output were the lowest in the holding generating the highest farm income.